Practical expressivism : a metaethical theory - Sinclair, Neil (Oxford University Press, 2021)
What is morality? Neil Sinclair argues that it is a purely natural interpersonal co-ordination device, whereby human beings express their attitudes in order to influence others' attitudes and actions. Sinclair shows that even if moral practice is fundamentally expressive, it can still possess the features that make morality appear objective.